Six steps in quality intervention development (6SQuID). Issue 5 (16th November 2015) - Wight, Daniel; Wimbush, Erica; Jepson, Ruth; Doi, Lawrence
Abstract : Improving the effectiveness of public health interventions relies as much on the attention paid to their design and feasibility as to their evaluation. Yet, compared to the vast literature on how to evaluate interventions, there is little to guide researchers or practitioners on how best to develop such interventions in practical, logical, evidence based ways to maximise likely effectiveness. Existing models for the development of public health interventions tend to have a strong social-psychological, individual behaviour change orientation and some take years to implement. This paper presents a pragmatic guide to six essential Steps for Quality Intervention Development (6SQuID). The focus is on public health interventions but the model should have wider applicability. Once a problem has been identified as needing intervention, the process of designing an intervention can be broken down into six crucial steps: (1) defining and understanding the problem and its causes; (2) identifying which causal or contextual factors are modifiable: which have the greatest scope for change and who would benefit most; (3) deciding on the mechanisms of change; (4) clarifying how these will be delivered; (5) testing and adapting the intervention; and (6) collecting sufficient evidence of effectiveness to proceed to a rigorous evaluation. If each of these steps is carefully addressed, better use will be made of scarce public resources by avoiding the costly evaluation, or implementation, of unpromising interventions.